Harmonisasi Pola Pengelolaan Keuangan Faskes Di Lingkungan Kementerian Pertahanan Dan TNI Dengan UU No. 44 Tahun 2009 Tentang Rumah Sakit - Sutarno (Faculty of Law Hang Tuah University, 2019)
Since the enactment of Law Number 24 of 2011 concerning the Social Security Organizing Agency, there has been a very fundamental change in terms of Health Services. Health facilities within the Ministry of Defense and TNI which also affect budget governance. This legal research is a normative law with sources of primary and secondary legal materials that aim to review and analyze the legal rules regarding the management of income income received by Health Facilities within the Ministry of Defense and the TNI based on Law Number 44 of 2009; and reviewing and analyzing conflicting norms for the use of the TNI Health Facility as of the enactment of Law Number 24 of 2011 concerning the Health Insurance Administering Body. The results showed that the TNI Hospital which is a health facility owned by the Government should be subject to the rules contained in RI Law No. 44 of 2009 concerning Hospitals.